Arquitectura y poesía : el complejo sagrado de Keushu y las Termas de Vals (2018)
"This thesis intends to recognize the poetic qualities of a pre-hispanic architecture case in the north of Perú and comparing them with the contemporary case of the Vals Therme in Switzerland, by the architect Peter Zumthor. The purpose is to search for characteristics of antique buildings where men complexity occupied a primary role."--Tomado del Formato de Documento de Grado.